Estimated Rate of Post-Operative Anastomotic Leak Following Colorectal Resection Surgery: A Systematic Review - Andrew Schiff; Brenna L Brady; Sudip K Ghosh; Sanjoy Roy; Charles Ruetsch; Elliott Fegelman (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Purpose: Anastomotic leak following colorectal resection surgery is associated with short and long-term negative patient outcomes, prolonged hospitalization, and increased healthcare costs. Various patient related and surgical factors are known to contribute to the development of postoperative anastomotic leaks. This study systematically reviewed the literature to assess the incidence of post-operative leak and identify patient factors associated with the development of leaks. Methods: Articles published from 1/1/2003 - 8/8/2015 reporting on post-operative anastomotic leak following colorectal resection surgery were identified in the Medline and Embase databases. The rate of post-operative leak, as well as patient and surgical characteristics, were extracted. Results: Forty-three articles met study inclusion criteria. Within the 14,102 cases, 867 patients experienced anastomotic leak, yielding an average leak rate of 6.1%. Patients were primarily male (57.0%) and had a mean age of 60.2 years. The majority of patients received a stapled anastomosis (70.9%), and most resection surgeries were performed for a diagnosis of cancer (80.7%). Comparison of patient characteristics with and without a post-operative leak revealed male gender, diabetes, open surgical procedures, and sutured anastomoses to be risk factors of anastomotic leak. Patients with anastomotic leak had a longer length of stay in the hospital and higher mortality rate than patients without a leak. Conclusions: Anastomotic leak remains a major concern in colorectal resection surgery and occurs in approximately 6.1% of cases. Both patient and surgical factors are associated with the development of post-operative anastomotic leak, which is linked to negative patient outcomes and increased mortality.